2020
DOI: 10.1039/d0cp02206c
|View full text |Cite
|
Sign up to set email alerts
|

Chemically directed structure evolution for crystal structure prediction

Abstract: The chemically directed structure evolution method uses chemical models to quantify the environment of atoms and vacancy sites in a crystal structure with that information used to inform how to modify the structure for crystal structure prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…We employ Crystal Structure Prediction (CSP) for 244 different compositions in the Li-Sn-S-Cl phase field (cyan tripods in Fig. 2b ) with the complementary algorithms of basin-hopping ChemDASH 22 , 39 , which explores the energy landscape, with starting ionic configurations based on hcp and rhombohedral lattices and evolutionary XtalOpt 40 exploring random and mutated (hybrid) ionic configurations drawn from a population of structures, spanning in total up to 1200 structures for each composition to maximize coverage of possible ionic arrangements. Both methods are coupled with VASP 41 for energy computation at the DFT level of accuracy (cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We employ Crystal Structure Prediction (CSP) for 244 different compositions in the Li-Sn-S-Cl phase field (cyan tripods in Fig. 2b ) with the complementary algorithms of basin-hopping ChemDASH 22 , 39 , which explores the energy landscape, with starting ionic configurations based on hcp and rhombohedral lattices and evolutionary XtalOpt 40 exploring random and mutated (hybrid) ionic configurations drawn from a population of structures, spanning in total up to 1200 structures for each composition to maximize coverage of possible ionic arrangements. Both methods are coupled with VASP 41 for energy computation at the DFT level of accuracy (cf.…”
Section: Resultsmentioning
confidence: 99%
“…In CSP with ChemDASH 39 , for each composition, the structure was initialized with anions (S 2− , Cl 1− ) located on a 2 × 2 × 2 or 3 × 2 × 2 grid in a close-packed arrangement and cations (Li 1+ , Sn 4+ ) occupying the interstitial sites. Up to 600 Li-Sn-vacancy and S-Cl atomic swaps were performed from initial structures and optimized geometrically with VASP to produce candidate structures for each composition.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that aligning the initial molecular dynamics velocities along the directions of soft phonon modes helps accelerate the search. , The minima hopping method has been used extensively to predict the structures of materials under pressure such as superconducting S x Se (1– x ) H 3 phases, binary intermetallics that are immiscible at 1 atm, and structural candidates for cold compressed graphite . Minima hopping should not be confused with the similarly named basin hopping method, which has been applied extensively to finite clusters and water-ice, and it is under active development for more complex systems. …”
Section: Computational Detailsmentioning
confidence: 99%
“…10,12 To improve the sampling efficiency, a variety of strategies have been proposed such as exploiting symmetry 15,16 and pseudosymmetry, 10 smart variation operators, clustering, 17 machine-learning interatomic potentials with active learning, 18 and designing chemically based swapping operators. 19 However, the scalability of these ab initio approaches remains an unsolved issue.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 10 years, CSP algorithms based on evolutionary algorithms and particle swarm optimization have led to a series of new materials discoveries. ,, However, these ab initio free energy-based global search algorithms have a major challenge that limits their success to relatively simple crystals (mostly binary materials or compounds with less than 20 atoms in the unit cell , ) because of their dependence on the costly DFT calculations of free energies for sampled structures. With a limited DFT calculation budget, it is a key issue to efficiently sample the atom configurations. , To improve the sampling efficiency, a variety of strategies have been proposed such as exploiting symmetry , and pseudosymmetry, smart variation operators, clustering, machine-learning interatomic potentials with active learning, and designing chemically based swapping operators . However, the scalability of these ab initio approaches remains an unsolved issue.…”
Section: Introductionmentioning
confidence: 99%